KOMPOSISI UNSUR DAN MINERAL DALAM PASIR BESI, RESIDU BAUKSIT DI PT. INDONESIA CHEMICAL ALUMINA (ICA) (ELEMENTAL COMPOSITION AND MINERALS IN IRON SAND, BAUXITE RESIDUE AT PT. INDONESIA CHEMICAL ALUMINA (ICA) - Imelda Hotmarisi Silalahi; Nikmatun Khasanah; Titin Anita Zaharah (Tanjungpura University, 2021)
Iron sand is obtained from one of the waste treatments stages of bauxite residue called red mud, operated at PT. Indonesia Chemical Alumina (PT. ICA). Preliminary analysis of the sand indicates that the main element contained in the sand is iron with a percentage of up to 60% and titanium at 10%. This study aims to determine the elemental composition and mineral characteristics of sand that was separated magnetically from the iron sand. Magnetic separation was carried out in two stages, namely separation using a weak magnets and strong magnets. The separation resulted in approximately 71% of strong magnetic sand. The rest was separated using the strong magnet giving almost 70% of weak magnetic sand while the residue is non-magnetic sand. The weak magnetic sand was analyzed using XRF and XRD to determine elemental composition as well as the type of mineral contained in the material. Elemental analysis showed that the weak magnetic sand contains 66.331% of iron, 13,120% of silicone, 9.216% of aluminum and 7.040% of titanium. The XRD analysis presented that crystalline phase in the sand consists of ilmenite, hematite, goethite, quartz and rutile.